(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. L’idioma della laicità - 3. Laicità e bilateralità - 4. La difficile convivenza con il favor religionis - 5. Gli Islam e l’ateismo - 6. Gli obblighi internazionali della laicità - 7. Conclusioni. Le potenzialità nascoste della laicità. Secularism and Bilateralism Thirty Years after the 1989 Landmark Constitutional Decision. The Italian Secularism tested by Islam and atheism ABSTRACT: In 1989 the Constitutional Court stated that secularism (laicità) is one of the supreme principles (principi supremi) of the Italian constitutional order. On the basis of articles 2, 3, 7, 8, 19 and 20 of the 1948 Constitution, the Court said that secularism does not affirm indifference of the State towards religions; rather, it sustains the protection of religious freedom in a context of cultural-confessional pluralism. With this essay the author examines the way the Italian supreme principle of secularism has developed in the last thirty years, especially in relation to the so-called bilateralism method (as stated in articles 7.2 and 8.3 of the Italian Constitution) and in the light of today’s pluralism, which is characterized by the presence of new collective organizations, such as those referring to Islam and atheism.